FINDING YOURSELF IN BOOKS AS TEENAGER: YOUNG ADULT LITERATURE AS SPRINGBOARD FOR SOCIAL RELEVANCE AND CLASSROOM RESEARCH - Tri Pramesti (Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract. Young adult literature is a relatively subgenre of pop literature. It develops along with the development of printing industry. Because this genre is for teenagers, the characters in young adult literature will be of 12-20 years old. The major themes are around the teenagerâ€™s lives, such as â€œbeauty meaningâ€ and â€œbody imageâ€, â€œbullyingâ€, and so on. Although this subgenre shows a rapid development, research on this subgenre are still few. This article discusses the characteristics of young adult literature, particularly on the current condition toward the readers. Keywords: teenlit, young adult literature, social relevance, classroom research